Pengaruh Daya Tarik Wisata dan Fasilitas Terhadap Keputusan Berkunjung di Destinasi Mice Puncak Siosar 2000 Kabupaten Karo - Rey Sebastian Tarigan; Ika Mary (JURNAL RISET MANAJEMEN (JURMA), 2024)
The Influence of Attractiveness and Facilities on Visiting Decisions at Puncak Siosar 2000 MICE Destinations, Karo Regency. This study aims to determine the effect of tourist attraction on the decision to visit the MICE Puncak Siosar 2000 destination, determine the effect of facilities on the decision to visit the MICE Puncak Siosar 2000 destination, determine the influence of tourist attraction and facilities on the decision to visit the MICE Puncak Siosar 2000 destination. This study uses a quantitative research method with multiple linear analysis. The variables used in this study are Attractiveness (X1), Facilities (X2), and Visit Decision (Y). Data collection was obtained by distributing questionnaires online to visitors who had visited Puncak Siosar 2000 using a accidental sampling technique, with predetermined characteristics. The scale measurement used in this study is the Likert Scale. The data in this study were processed with the help of the IBM SPSS Statistics 26 for Windows application. The results showed that the Attractive Variables (X1) and Facilities (X2) had a positive and significant effect on Decision (Y) both partially and simultaneously. This is evidenced by the results obtained based on hypothesis testing. The results of the t test for attractiveness with a significant level at α = 0.05 with tcount > ttable (6.227 > 1.661) and facilities with a significant level at α = 0.05 with tcount > ttable (5.552 > 1.661). While the results of the F test are proven by a significant level at α = 0.05 with fcount > ftable (52.338 > 3.09).